THE ART OF COMICS AND GRAFFITI – A MODERN WORLDVIEW IN GRAPHIC DESIGN - Гула, Є. П. (Art and Design, 2021)
The purpose – to investigate lines and features of definition of the main defining characteristics of art of the comic book and graffiti in the context of modern outlook in graphic design. Methodology.General scientific methods of a research, analytical, typological, semantic and comparative analysis – are applied to terminological definition of a conceptual framework of graphic design and designation of its theoretical and art criticism application. Results. On the basis of the analysis of scientific sources of the modern foreign and Ukrainian art of the comic book and graffiti generally aspects of interpretations of these welfare concepts, their historical sources in the world and Ukraine are estimated. The perspective of a ratio of art of the comic book and graffiti and world outlook values of modern design is updated. Formation of art both comics, and graffiti and also corresponding design trends is directly connected with the transition to a postmodern (approximately the second half of the 20th century) which is followed by formation of a certain number of social groups and informal movements of artists ("writer"). The scientific novelty consists in consideration of art of the comic book and graffiti as certain welfare community. It is established that both comics, and graffiti were the communication medium and identifications for representatives of these separated groups: comics – for intellectual communities, graffiti – for conditionally "street". Practical significance. The summed-up modern scientific determination of graphic design. Results of a research can be used in practice of teaching graphic design, art of the comic book and other graphic disciplines.